BALINESE FOLKLORE AS A LEARNING DEVICE TO ENHANCE STUDENTS' SPEAKING SKILL AND SOCIO-LINGUISTIC COMPETENCE - Widiastuti , Ida Ayu Made Sri (Denpasar Institute, 2019)
Folklore is traditional oral stories that are passed down from one person to another for generations in society. Folklore contains local wisdom, noble characters, cultural heritage, and rich socio-linguistic features that should be preserved for society. Folklore as one of the teaching materials may improve students’ cultural and linguistic awareness as well as linguistic competence. The present study was conducted to attempt at improving speaking and socio-linguistic competence through implementing Balinese folklore in the English language classroom. This study was triggered by the fact that the students have low ability in speaking and socio-linguistic competence. The results of the analysis of the questionnaire clearly showed that the students’ attitudes and motivation in learning speaking through Balinese folklore were improved significantly. This study implies that Balinese folklore is an effective teaching model to improve the students’ speaking skills and socio-linguistic competence, Therefore, the use of Balinese folklore should be carefully considered as an effort to optimally maximize students' engagement in language learning.